Perancangan Sistem Peramalan Jumlah Produksi Keripik Menggunakan Metode Moving Average - Sri Ipnuwati (Universitas Mitra Indonesia, 2021)
AbstractA company in the field of product sales or distribution services requires a strategic decision to achieve what is the goal. One of the most important things to make this happen is to estimate or forecast the amount of sales or production of the goods or services produced. This is because the sale of a product is basically not only the use of the right forecasting method but also the production planning process, market appraisal, promotion and marketing policies. One form of business that is engaged in the sale of banana chip snack products, where there is often a shortage of stock inventory due to not being able to predict or predict before production. Therefore, the forecasting method is to find out how much product needs are provided in order to meet consumer needs so that there is no inventory void. This study proposes an information system to predict the number of chips production using the Moving Average method in determining the amount of chips production and from the research results, the predictive information system for forecasting the number of chips production is built using the Java programming language and MySQL Yog Enterprise. The information system can run in accordance with the original purpose so that this system can help companies and their users in obtaining information to produce chips while replacing manual systems.